perbedaan hasil rias wajah karakter tua menggunakan kosmetik body painting dan pensil alis - cindy melynandra (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
This study is on the makeup of old female characters performed by female students, lack of female understanding of wrinkle making techniques and proper selection of cosmetics in makeup of old female characters, this study aims to analyze the makeup of old female characters using body painting cosmetics and eyebrow pencil, and to find out the differences in the makeup of old female characters between the use of cosmetic body painting and eyebrow pencil. This type of research is a quasi experiment with a non equivalent control group design. The sampling technique is done by purposive sampling technique. The results of the analysis showed that in the experimental group 1 the use of cosmetic body painting (X1) with an average value of 3.5778 with a very good category. Furthermore, in the experimental group 2 using eyebrow pencil (X2) with an average value of 2.2444 with an unfavorable category.